Mitochondrial metabolism - neglected link of cancer transformation and treatment - Pokorný, J; Jandová, A; Nedbalová, M; Jelínek, F; Cifra, M; Kučera, O; Havelka, D; Vrba, J; Vrba, J; Coček, A; Kobilková, J (Prague medical report, 2012)
Physical processes in living cells were not taken into consideration among the essentials of biological activity, regardless of the fact that they establish a state far from thermodynamic equilibrium. In biological system chemical energy is transformed into the work of physical forces for various biological functions. The energy transformation pathway is very likely connected with generation of the endogenous electrodynamic field as suggested by experimentally proved electrodynamic activity of biological systems connected with mitochondrial and microtubule functions. Besides production of ATP and GTP (adenosine and guanosine triphosphate) mitochondria form a proton space charge layer, strong static electric field, and water ordering around them in cytosol - that are necessary conditions for generation of coherent electrodynamic field by microtubules. Electrodynamic forces are of a long-range nature in comparison with bond and cohesive forces. Mitochondrial dysfunction leads to disturbances of the electromagnetic field; its power and coherence may be diminished, and frequency spectrum altered. Consequently, defective electrodynamic interaction forces between cancer and healthy cells may result in local invasion of cancer cells. Further deformation of interaction forces connected with experimentally disclosed spatial disarrangement of the cytoskeleton and disordered electrodynamic field condition metastatic process. Cancer therapeutic strategy targeting mitochondria may restore normal physiological functions of mitochondria and open the apoptotic pathway. Apoptosis of too much damaged cancer cells was observed. Considerable experience with DCA (dichloroacetate) cancer treatment in humans was accumulated. Clinical trials should assess DCA therapeutic potential and collect data for development of novel more effective drugs for mitochondrial restoration of various cancers.
Keywords: elektrofyziologické jevy; Neoplasms; Dichloroacetic Acid; lidé; guanosintrifosfát; Electrophysiological Phenomena; adenosintrifosfát; energetický metabolismus; Guanosine Triphosphate; Energy Metabolism; Adenosine Triphosphate; kyselina dichloroctová; mitochondrie; nádorová transformace buněk; Humans; nádory; Mitochondria; Microtubules; mikrotubuly; Cell Transformation, Neoplastic